Perkembangan dan Pemetaan Riset Wakaf Produktif: Analisis Bibliometrik : Development and Mapping of Productive Waqf Research: A Bibliometric Analysis - Azwar, Azwar; Khaerul Aqbar (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2024)
This study aims to map and analyze the development of research on productive waqf using bibliometric methods in reputable international publications. The research employs quantitative methods through bibliometric analysis on the Scopus database from 2004 to 2024. The results show a significant increase in publications on productive waqf in recent years. The most productive author/researcher in this area and the most frequently cited is A. Ascarya. In terms of publication media, the Journal of Islamic Accounting and Business Research has emerged as a popular platform. Topic mapping results reveal that the keyword "Indonesia" is a focal point in the study of productive waqf. Topics closely related to Indonesia, such as potential, productive waqf, cash waqf, empowerment, development, and company management, are important aspects in the management and empowerment of waqf in the country. Newer research areas, such as empirical evidence, financing models, cash waqf literacy, cash waqf, and Baitul Maal wat Tamwil, have likely been developing in recent years. In terms of density, topics like impact, empirical evidence, and financing models appear to be less explored and may present promising research areas for the future.